2018
DOI: 10.14735/amko201895
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNAs as Regulators of the Mitogen-activated Protein Kinase (MAPK) Pathway in Cancer

Abstract: Considering the role of this pathway in the pathogenesis of several cancers, alterations in lncRNA expression lead to changes in MAPK pathway resulting in inhibition of apoptosis and induction of cell proliferation and migration. Moreover, some lncRNAs participate in cross-talk between MAPK and other cancer-related pathways, such as PI3K/Akt pathway through regulation of certain shared proteins between these pathways. Based on the availability of certain anticancer drugs that modulate this pathway, identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…Notably, the present study demonstrated that lncRNA GATA6-AS, which has an important regulatory role in the growth of endothelial cells (10), may also participates in the metastasis of cervical squamous cell carcinoma. It was determined that the role of GATA6-AS in cervical squamous cell It has been reported that lncRNAs serve key roles in normal physiological processes and pathological changes (15).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Notably, the present study demonstrated that lncRNA GATA6-AS, which has an important regulatory role in the growth of endothelial cells (10), may also participates in the metastasis of cervical squamous cell carcinoma. It was determined that the role of GATA6-AS in cervical squamous cell It has been reported that lncRNAs serve key roles in normal physiological processes and pathological changes (15).…”
Section: Discussionsupporting
confidence: 50%
“…As a key member of the mitogen-activated protein kinase signaling pathway, mitogen-activated protein kinase kinase 4 (MTK-1) participates in critical cell developmental processes and functions (9). It has been demonstrated that long non-coding RNAs (lncRNAs), a subgroup of non-coding RNAs composed of >200 nucleotides, are critical regulators of mitogen-activated protein kinase in cancer development (10). GATA binding protein 6 antisense (GATA6-AS) is a recently identified lncRNA that is involved in the regulation of the growth of endothelial cells (11); however, to the best of our knowledge, the involvement of GATA6-AS in other physiological or pathological processes remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Genomewide association studies have recently mapped a large proportion of disease‐ or trait‐associated single nucleotide polymorphisms outside the protein coding regions of the genome, often in or near genes transcribed into lncRNAs (Bartonicek et al, ; Gong, Liu, Zhang, Miao, & Guo, ). There are bona fide examples of lncRNA linked to one or multiple hallmarks of cancer in a variety of cancers, including melanoma, in which many emerge as regulators of the MAPK and PI3K pathways (for review, Huang et al, ; Leucci, Coe, Marine, & Vance, ; Schmitt & Chang, ; Tasharrofi & Ghafouri‐Fard, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are bona fide examples of lncRNA linked to one or multiple hallmarks of cancer in a variety of cancers, including melanoma, in which many emerge as regulators of the MAPK and PI3K pathways (for review, Huang et al, 2018;Leucci, Coe, Marine, & Vance, 2016;Schmitt & Chang, 2016;Tasharrofi & Ghafouri-Fard, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We further verified the combined effect of MALAT1 and miR-503 on NPC proliferation, apoptosis, and ECM degradation, as well as the involvement of the MAPK pathway. Upon IL-1β stimulation, MALAT1 overexpression remarkably enhanced the NPC proliferation and NPC number ( Previous studies have shown that MALAT1 can affect the MAPK/AP1 signaling pathway [19], which is an important pathway for IVD [15]. Therefore, we examined the relationship between MALAT1, miR-503 and the MAPK pathway.…”
Section: Malat1 Inhibits Mir-503 To Regulate the Function Of Npcs Andmentioning
confidence: 99%